Monitoring and Evaluation for World Bank Agricultural Research and Extension Projects : A Good Practice Note - Rajalahti, Riikka; Woelcke, Johannes; Pehu, Eija (Washington, DC : World Bank, 2022)
This Good Practice Note aims to assist Task Teams of the World Bank and their colleagues in the client countries develop and implement effective monitoring and evaluation (M&E) systems for agricultural research and extension projects and programs. The chapters in this Note provide a step-by-step guide for achieving that objective, with emphasis on the World Bank M&E requirements and the specific nature of agricultural research and extension projects. Chapter 1 titled "Challenges for M&E Systems in Agricultural Research and Extension Projects" and Appendix 1 titled "Narratives of New Approaches and Instruments in ARE Systems" discuss the M&E challenges in agricultural research and extension projects; and provide additional information on the forces driving the changes in agricultural research and extension systems as well as on the typical approaches and instruments applied in agricultural research and extension systems and projects. The Note emphasizes the World Bank's M&E Requirements at the design stage, namely the introduction of the Results Framework and the associated requirements in the Project Appraisal Document. Chapter 2 describes the key issues in the results framework which are (a) development of a clear project development objective and project components, and (b) the importance of developing measurable and realistic project outcome and intermediate outcome indicators. In addition, Appendix 2 summarizes the Bank's M&E steps throughout the Project Cycle and Appendix 3 provides further details and references on the Logical Framework. A list of indicators, with emphasis on institutional, social, and environmental sustainability, and data sources for agricultural research and extension Projects are provided in Appendix 4.